Laws and Issues in Protecting Children from Sexual Exploitation: A Case Study in Thailand - Sriwiset , Ploypailin (Journal of Ecohumanism, 2024)
Today, violations of children’s rights have become more intense and have taken on new forms. Child protection laws provide a legal framework designed to shield children from harm and abuse, especially sexual abuse. These laws define the rights and responsibilities of parents, the state, and others involved with children. The objectives of this research are 1) to study the legal measures regarding child protection laws and issues related to the sexual exploitation of children in Thailand, compared to international and foreign laws, and 2) to explore ways to amend and improve Thai laws on child protection from sexual exploitation of children in Thailand to align with international standards. The study found that significant child protection laws in Thailand include: 1) the Child Protection Act, B.E. 2546 (2003), 2) the Anti-Human Trafficking Act, B.E. 2551 (2008), and 3) the Domestic Violence Victims Protection Act, B.E. 2550 (2007). However, due to various factors and ambiguous definitions, the child protection laws have not fully achieved their objectives, allowing offenders to receive lighter punishments. Therefore, this article examines ways to amend and improve Thai child protection laws regarding sexual exploitation of children to be consistent with international law. The recommendations on legal action can be divided into three approaches: legal measures and child protection issues regarding sexual exploitation of children, child protection issues from sexual exploitation, and measures to suppress those who sexually exploit children.